Myroides odoratimimus Forms Structurally Complex and Inherently Antibiotic-Resistant Biofilm in a Wound-Like in vitro Model - Pompilio, Arianna; Galardi, Giuseppe; Verginelli, Fabio; Muzzi, Maurizio; Di Giulio, Andrea; Di Bonaventura, Giovanni (Frontiers in Microbiology, 2017)
Myroides odoratimimus is an aerobic, non-fermenting Gram-negative multidrug-resistant bacterium widely distributed in nature that rarely causes infections in immunocompromised patients. We recently described in a diabetic patient a case of recurrent calcaneal ulcer infection caused by a M. odoratimimus strain showing potential for biofilm formation. For the first time, we therefore evaluated the ability of M. odoratimimus to form biofilm under different pH values and glucose concentrations using an in vitro “skin-like” model, and its susceptibility to levofloxacin, meropenem, and tigecycline. The expression of some antibiotic-resistance related genes was also monitored by RT-PCR during planktonic-to-biofilm transition. Our results indicated that M. odoratimimus can produce relevant amounts of biofilm biomass, in a time-dependent manner, especially at acidic pH and regardless of glucose concentration tested. The comparative analysis of MIC and MBC values between planktonic and sessile cells showed that resistance to antibiotics increased during the planktonic-to-biofilm transition. Viable cell count indicated that none of the tested antibiotics were able to completely eradicate preformed biofilms, although meropenem and levofloxacin were the most active causing a significant, dose independent, reduction of biofilm’s viability, as also confirmed by microscopic analysis. RT-PCR showed that antibiotic-resistance related gyrA and acrB genes are over-expressed during the transition from planktonic to sessile (biofilm) lifestyle. Overall, our findings showed that M. odoratimimus can form relevant amounts of inherently antibiotic-resistant biofilm under conditions relevant to wound site, therefore suggesting a role in the pathogenesis of chronic ulcer infections.